2020
DOI: 10.22159/ijpps.2020v12i5.37008
|View full text |Cite
|
Sign up to set email alerts
|

Synergism Between Probiotics and Herbs to Manage Type 2 Diabetes in Rats

Abstract: Objective: This study aims to explore the adjuvant effect of multi-strain probiotics with either saffron, cardamom, ginger, or cinnamon herbs to achieve synergistic management for controlling type 2 diabetes (T2D). Methods: Eighty-eight adult male, Wistar rats were used. Eight rats were kept as healthy control. Eighty rats were used to induce type 2 diabetic rats (T2DR) and were randomly assigned to ten groups. One group was an offer to 0.2 ml multi-strain probiotics orally. The rest of T2DR were gavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Comparing the content of bioactive phenolic compounds expressed as TPC among the studied plants, the lowest TPC value was determined in cardamom rhizome and correlates well with previously published studies [ 24 , 33 , 38 ]. The low TPC content in cardamom can be explained by the fact that the flavonoid diosmin, the most important single phenolic compound [ 38 ], is practically insoluble in water and poorly soluble in polar organic solvents (e.g., EtOH, MeOH) [ 67 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Comparing the content of bioactive phenolic compounds expressed as TPC among the studied plants, the lowest TPC value was determined in cardamom rhizome and correlates well with previously published studies [ 24 , 33 , 38 ]. The low TPC content in cardamom can be explained by the fact that the flavonoid diosmin, the most important single phenolic compound [ 38 ], is practically insoluble in water and poorly soluble in polar organic solvents (e.g., EtOH, MeOH) [ 67 ].…”
Section: Resultssupporting
confidence: 89%
“…Ginger is also rich in vitamins A and C, while the other compounds such as fatty acids, proteins, carbohydrates, fiber, ash, minerals (potassium, calcium, phosphorus, magnesium, iron) are present in lower amounts [ 23 ]. Recent studies have shown various pharmaceutical effects of the ginger rhizome, and the most important is the proven antidiabetic effect [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Ali et al [34], aqueous ginger extracts showed anti-hyperglycemia and anti-inflammatory activities when tested alone against type 2 diabetes in rats, in vivo [35]. When the same aqueous extracts were combined with probiotics of eight good bacteria, they portrayed synergism.…”
Section: Antidiabetic Activities Of Ginger Combinationsmentioning
confidence: 96%
“…Anxiety and depression are increased by mercury II chloride (HgCl 2 ) in mice [39]. In a study by Benkermiche et al [40], ginger extracts combined with black cumin (Nigella sativa L.) oil showed prophylaxis synergistic effects on anxiety and depression behavior in Wistar rats that had been exposed to HgCl 2 [34]. This could be attributed to the pure compounds like 6-gingerol, isolated from ginger, which has shown neuroprotective effects in rodents [41], and the antidepressant activities of thymoquinone, the active ingredient in N. sativa which act synergistically when combined [14].…”
Section: Antidepressant Activities Of Ginger Combinationsmentioning
confidence: 99%